The Implementation of Steam Integrated Thematic Learning Based on Local Wisdom of Kapuas Hulu in Elementary School - Oktoriyadi, Oktoriyadi (Universitas Tanjungpura, 2020)
Kapuas Hulu is one of the districts in Indonesia whose children are still digitally discriminated against in the 21st century, especially disadvantaged villages. Nevertheless, students must think critically and creatively in responding to their limitations and socio-cultural conditions to solve the problems at hand. The principle of global thinking and acting locally and having 4C competencies (critical thinking, communication, collaboration, creativity) as 21st-century life skills are very much needed by students to face competition in the current and future industrial revolution 4.0 era. To prepare such students, one of them was by implementing STEAM integrated thematic learning based on local wisdom. STEAM-based learning could train the abilities and talents of students facing 21st-century problems (Danang Wijaya, et al. 2015: FP-87). The results of the study concluded that integrated STEAM thematic learning based on local wisdom was suitable for application in elementary schools. Implementation in learning was done through integrating the content and context of Kapuas Hulu's local wisdom with the scientific disciplines contained in STEAM and the basic competencies of the content of the lessons in the existing themes to produce designs or products of local wisdom. The impact of its implementation was to be able to develop students' cognitive, affective, and psychomotor abilities that support 21st-century life skills in facing competition in the industrial revolution era 4.0 with the principles of global thinking and acting locally.